Disability, Vocation, and Prophetic Witness - Swinton, John (Theology today, 2020)
This paper builds on Frances Young’s suggestion that people with profound intellectual disability have a prophetic vocation. It explores the idea of vocation using the experience of intellectual disability as a critical hermeneutic that brings to the fore a perspective that views vocation as something that includes all of the Body of Christ and not just the head. The intention is to offer a different more theologically and practically inclusive perspective on vocation that might enable us to create communities where each member's vocation was valued and enabled.